SOCIALIZATION OF THE ECO-FRIENDLY-HOUSE PROGRAM TO SUPPORT ENVIRONMENTAL HEALTH IN KAYU MERAH VILLAGE, TERNATE CITY - Sherly Asriany; Anthonius F. Raffel; Utdin Furqon Amali (Jurnal Abdisci, 2024)
Ternate city be classified as a moderate to low level of poverty. Education level in the Kayu Merah of Ternate neighborhood is as follows: 884 people have completed primary school, 1,161 have done secondary school, and 502 have a university degree. We're working with the community in Kayu Merah on this PKM Programme. PKM method involves identifying the issues that need to be addressed. PKM activities include awareness-raising, training and active involvement in planned activities, such as fostering critical awareness among the community about the importance of active participation in environmental management and increasing knowledge and understanding of eco-friendly-house. We've seen the formation of community groups capable of managing environmental health, a rise in awareness about eco-friendly-house, and the early stages of a professional, organised community of environmentally conscious individuals. PKM was carried out as planned, with the aim of providing understanding of the eco-friendly-house programme and promoting environmental health.